La dinámica familiar y estilos de crianza: pilares fundamentales en la dimensión socioafectiva (2019)
The objective of this article is to give an account of the imaginaries and representations of families built by children and parents and their relationship with the socio-affective dimension. The study was based on a qualitative paradigm, emphasizing the case study research strategy. The observation and the semi-structured interview were used as information gathering techniques in the participants, who were 9 children and their respective parents or caregivers. It was obtained that the educational models influence the socio-affective development and the different behaviors of the children, and it was concluded that the children who are under authoritarian educational models, tend to be isolated from the social group of reference and those who are educated under democratic educational models are likely to be more autonomous and manage to socialize more easily.